IgM-Enriched Human Intravenous Immunoglobulin-Based Treatment of Patients With Early Donor Specific Anti-HLA Antibodies After Lung Transplantation. Issue 12 (December 2016) - Ius, Fabio; Sommer, Wiebke; Kieneke, Daniela; Tudorache, Igor; Kühn, Christian; Avsar, Murat; Siemeni, Thierry; Salman, Jawad; Erdfelder, Carolin; Verboom, Murielle; Kielstein, Jan; Tecklenburg, Andreas; et al.
Abstract : Background: At our institution, until April 2013, patients who showed early donor specific anti-HLA antibodies (DSA) after lung transplantation were preemptively treated with therapeutic plasma exchange (tPE) and a single dose of Rituximab. In April 2013, we moved to a therapy based on IgM-enriched human immunoglobulins (IVIG), repeated every 4 weeks, and a single dose of Rituximab. Methods: This observational study was designed to evaluate the short-term patient and graft survival in patients who underwent IVIG-based DSA treatment (group A, n = 57) versus contemporary patients transplanted between April 2013 and January 2015 without DSA (group C, n = 180), as well as to evaluate DSA clearance in IVIG-treated patients versus historic patients who had undergone tPE-based treatment (group B, n = 56). Patient records were retrospectively reviewed. Follow-up ended on April 1, 2015. Results: At 6 months and 1 year of follow-up, group A had a survival similar to group C ( P = 0.81) but better than group B ( P = 0.008). Group A showed statistically nonsignificant trends toward improved freedom from pulsed-steroid therapy and biopsy-confirmed rejection over groups B and C. The DSA clearance was better in group A than group B at treatment end (92% vs 64%; P = 0.002) and last DSA control (90% vs 75%; P = 0.04). Conclusions: Patients with new early DSA but without graft dysfunction that are treated with IVIG and Rituximab have similarly good early survival as contemporary lung transplant recipients without early DSA. The IVIG yielded increased DSA clearance compared with historic tPE-based treatment, yet spontaneous clearance of new DSA also remains common. Abstract : Combination treatment of IgM enriched human immunoglobulins (IVIG) and a single dose of rituximab significantly reduced the incidence of de novo DSA production after lung transplantation compared to historical therapeutic plasma exchange and a single dose of rituximab. Supplemental digital content is available in the text.